Heat-transfer performance of a cooling tube with an obstacle for protection under frosting conditions - Katsuyoshi FUKIBA; Sota SATO (Journal of Thermal Science and Technology, 2018)
Fundamental experiments were conducted on a cooling tube with an obstacle using liquid nitrogen as the coolant under a frost-formation condition. The background of this study is the development of a heat exchanger for an air-breathing engine, which cools the air using a cryogenic fuel. The obstacle is located in front of the cooling tube. The main purpose of the obstacle is to protect the cooling tube against damages due to foreign objects. The experimental results obtained using an obstacle with a V-shaped cross section show that the obstacle helps in reducing the pressure loss and improving the heat-transfer performance if the distance between the obstacle and the cooling tube is optimally selected. The experiments conducted using obstacles with several types of cross sections show that one of these obstacles with an arrowhead cross section is effective in suppressing the pressure loss, mitigating an adverse effect on the heat-transfer performance, and protecting the cooling tube against damages due to foreign objects.